Correlation of the solid-state reactivities of racemic 2,4(6)-di-O-benzoyl-myo-inositol 1,3,5-orthoformate and its 4,4 `-bipyridine cocrystal with their crystal structures - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica Section C-Structural Chemistry, 2014)
Racemic 2,4(6)-di-O-benzoyl-myo-inositol 1,3,5-orthoformate, C21H18O8, (1), shows a very efficient intermolecular benzoyl-group migration reaction in its crystals. However, the presence of 4,4 `-bipyridine molecules in its cocrystal, C21H18O8 center dot C10H8N2, (1)center dot BP, inhibits the intermolecular benzoyl-group transfer reaction. In (1), molecules are assembled around the crystallographic twofold screw axis (b axis) to form a helical self-assembly through conventional O-H center dot center dot center dot O hydrogen-bonding interactions. This helical association places the reactive C6-O-benzoyl group (electrophile, El) and the C4-hydroxy group (nucleophile, Nu) in proximity, with a preorganized El center dot center dot center dot Nu geometry favourable for the acyl transfer reaction. In the cocrystal (1)center dot BP, the dibenzoate and bipyridine molecules are arranged alternately through OH center dot center dot center dot N interactions. The presence of the bipyridine molecules perturbs the regular helical assembly of the dibenzoate molecules and thus restricts the solid-state reactivity. Hence, unlike the parent dibenzoate crystals, the cocrystals do not exhibit benzoyl-transfer reactions. This approach is useful for increasing the stability of small molecules in the crystalline state and could find application in the design of functional solids.
Keywords: acyl transfer; cocrystal; crystal structure; design of functional solids; helical assembly; hydrogen bonding; myo-inositol; solid-state reactions

Cocrystallization of 2,3-dihydroxynaphthalene with its para-, meta-, and ortho-ditoluates: insight into cocrystal formation and clues for the construction of supramolecular assemblies capable of intermolecular acyl group transfer reactivity - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2015)
2,3-Dihydroxynaphthalene forms 2:1 cocrystals with its p-ditoluate and 1:1 cocrystals with its m-ditoluate but not with the o-ditoluate. In 2:1 cocrystals of the p-ditoluate, naphthalene diol molecules form a dimeric motif through OH...O hydrogen bonding interactions. The adjacent dimers sandwich the molecules of p-ditoluate through C-H...pi interactions. In 1:1 cocrystals of the m-ditoluate, naphthalene diol molecules generate a zigzag pattern through O-H...O hydrogen bonding interaction involving -OH of the diol and the C=O of the m-ditoluate. Intermolecular toluoyl group transfer reaction was more facile in cocrystals of the p-ditoluate as compared to cocrystals of the m-ditoluate. This difference in reactivity is consistent with the relative geometry of the electrophile (El, C-O) and the nucleophile (Nu, OH) in these cocrystals. A comparison of the cocrystallization behavior and structure of the two cocrystals with their constituents suggests that the position of the methyl group is crucial for cocrystal formation. A survey of the CSD revealed that the incidence of polymorphism and cocrystals formation decreases (number of hits) in the order para- > ortho- > meta- for disubstituted benzene derivatives. This suggests that compounds prone to exhibit polymorphism have more propensities to form cocrystals as compared to those that resist polymorphism. This information could be useful while selecting cocrystal formers and construction of supramolecular functional assemblies with desired properties.

Cocrystallization of 2,3-dihydroxynaphthalene with its para-, meta-, and ortho-ditoluates: insight into cocrystal formation and clues for the construction of supramolecular assemblies capable of intermolecular acyl group transfer reactivity (vol 15, pg 12 - Tamboli, Majid I.; Bahadur, Vir; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Crystal Growth & Design, 2019)

Silver-catalyzed cascade cyclization/1,6-conjugate addition of homopropargyl sulfonamides to p-quinone methides: an approach to diverse 3-diarylmethine substituted dihydropyrroles - Shirsath, Sachin R.; Ghotekar, Ganesh S.; Bahadur, Vir; Gonnade, Rajesh G.; Muthukrishnan, M. (Journal of Organic Chemistry, 2020)
A silver-catalyzed cycloisomerization/1,6-conjugate addition of homopropargyl sulfonamides to p-quinone methides to access diverse diarylmethine substituted dihydropyrroles has been disclosed. The reaction pathway involves an intramolecular cascade cyclization of homopropargyl sulfonamides to generate a highly reactive dihydropyrrole intermediate in situ followed by conjugate addition with p-quinone methides. This method provides an efficient and scalable route for the synthesis of 3-diarylmethine substituted dihydropyrroles, in one pot.

Construction of two-component chemically reactive supramolecular assemblies-acyl migration reactions in cocrystals of napthalene-2,3-diol and its diesters - Bahadur, Vir; Gonnade, Rajesh G.; Tamboli, I. Majid; Krishnaswamy, Shobhana; Shashidhar, Mysore S. (ChemPlusChem, 2021)
Reactions in solids are of contemporary interest due to applications in pharmaceutical industries to environmental sustainability. Although several reactive crystals that support chemical reactions have been identified and characterized, the same cannot be said about reactive cocrystals. Earlier we correlated the facile acyl group transfer reactions in crystals with supramolecular parameters obtained from the crystal structures. The structure-reactivity correlation revealed the requirement of proper juxtaposition of electrophile (C=O) and the nucleophile (OH) with distance (similar to 3.2 angstrom) and angle (similar to 90 degrees) along the chain structure. The current article describes the preparation of cocrystals that are capable of supporting intermolecular acyl group transfer reactions in a group of structurally similar molecules. The cocrystals of naphthalene 2,3-diol and its corresponding diesters showed a facile solid state acyl transfer reaction, which has been well correlated with their crystal structures.
Keywords: Acylation; domino reactions; intermolecular interactions; reaction in cocrystal; solid-state reactions; X-ray diffraction

Lead-free zero dimensional tellurium(iv) chloride-organic hybrid with strong room temperature emission as a luminescent material - Biswas, Anupam; Bakthavatsalam, Rangarajan; Bahadur, Vir; Biswas, Chinmoy; Mali, Bhupendra P.; Raavi, Sai Santosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Materials Chemistry C, 2021)
Despite the current progress in `Pb-free' low dimensional main group metal halide based luminescent materials, it is challenging to synthesize Te(iv) halide hybrids with strong ambient emission with excitation features in the visible range as efficient and stable phosphors for potential lighting applications. Reported here is a (benzyltriethylammonium)(2)TeCl6 zero dimensional hybrid material with excitation features in the visible range and strong room temperature, broadband, intrinsic luminescence (PLQY similar to 15%) arising due to self-trapped excitons (STEs). Furthermore, a proof-of-concept LED architecture demonstrates successful optical down-conversion with a visible light excitation source. Here, exclusive adoption of a `regular' octahedral Te(iv)-halide unit structure with minimal static distortion provides a unique opportunity to unmask the role played by 5s(2) lone pair electrons in shaping the emissive properties. This effort may open up new avenues towards unravelling the role of lone pair stereoactivity in controlling the PLQY in low dimensional hybrids that has proven to be challenging for the reported (Sb, Sn) based low dimensional 5s(2) metal halide hybrid materials.

Metal halide structure and the extent of distortion control the photo-physical properties of luminescent zero dimensional organic-antimony(iii) halide hybrids - Biswas, Anupam; Bakthavatsalam, Rangarajan; Mali, Bhupendra P.; Bahadur, Vir; Biswas, Chinmoy; Raavi, Sai Santosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Materials Chemistry C, 2021)
Antimony(iii) halide based zero dimensional hybrids have gained attention as broadband emitters. Until now, quadrangular pyramidal SbX5 based and octahedral SbX6 based 0D hybrids have been reported utilizing different organic ligands demonstrating some structural tunability affecting their emissive properties. Utilizing a common organic ligand, here we demonstrate the structural tunability (quadrangular pyramidal, octahedral, or a combination thereof) of the metal halide unit in Sb(iii)Cl 0D hybrids with contrasting photo-physical properties (broadband, Stokes shift, strong/weak colored emission). The structure-property-mechanism correlation of the synthesized compounds [1 (C12H52Cl18N8O4Sb3; tris Sb green); 2 (C12H50Cl14N8O3Sb2; tris Sb red); 3 (C24H88Cl25N16O4Sb3; tris Sb yellow)] identifies crucial factors that control their emissive properties. The X-ray analysis reveals the structure (1-octahedral; 2-quadrangular pyramidal; 3-combination thereof) and the order of the extent of structural distortion as 1-3 MUCH LESS-THAN 2. The metal halide coordination environment asymmetry and its structure are observed to dictate PL emission energy (1-green; 2-red; 3-yellow) as supported by a qualitative Molecular Orbital scheme. The extent of structural distortion guides the observed Stokes shifts (1-165 nm; 2-290 nm; 3-200 nm; 1-3 < 2). Interestingly, the extent of distortion is found to be well correlated with the observed PLQY (1-45%; 2-6%; 3-43%; 1-3 >> 2). This report clearly demonstrates the structural tunability and the effect of the metal halide unit structure/distortion in shaping the emissive properties of 0D organic Sb(iii) halide hybrids.

Synthesis, characterization and single crystal x-ray structures of trifluroacetylacetonate copper(ii) complexes - Kumari, Neha; Bahadur, Vir; Butcher, Raymond J.; Kumbhar, Anupa A. (Journal of Chemical Crystallography, 2022)
{Three Cu(II) complexes of 1,1,1-trifluoroacetylacetonate, viz. [Cu(TFACAC)(2)(MeOH)] (1), [Cu(TFACAC)(2)(py)] (2) and [Cu(TFACAC)(2)(DABCO)] (3) were synthesized and characterized by elemental analysis, IR, UV-Visible spectroscopy and cyclic voltammetry. Structures of complexes 1-3 were established by single crystal X-ray diffraction wherein 1 and 2 adapt square pyramidal geometry. Complex 1 crystallizes in triclinic space group P-(1), with a = 8.5059(6) angstrom
Keywords: Copper(II) complexes; crystal structure; cyclic voltammetry; DABCO; Pyridine; Trifluoroacetylacetone